Balok Kayu Sengon Laut dengan Perkuatan CFRP pada Serat Tarik dan Tekan Ditinjau terhadap Pembebanan Lentur - Aditya Purnama; Danang Hadi Nugroho (Universitas Batanghari Jambi, 2026)
The increasing demand for economical and environmentally friendly housing has driven the use of local materials such as sengon laut (Falcataria moluccana) as structural elements in buildings. Sengon laut is a fast-growing and relatively pest-resistant species, but its flexural strength is relatively low. To improve its performance, this study analyzed the effect of using Carbon Fiber Reinforced Polymer (CFRP) as a reinforcing material in sengon laut beams under flexural loading. The study began with laboratory tensile testing of sengon laut, CFRP, and epoxy resin to obtain tensile strength, elongation, and modulus of elasticity. The test data were then used as input for material properties in a numerical analysis using the Midas Gen 2019 program. The analysis was conducted on two beam models: an unreinforced beam and a beam with CFRP reinforcement in both tension and compression. Simulation results showed that the sengon laut beam with CFRP reinforcement had significantly increased flexural capacity and stiffness compared to the unreinforced beam. Maximum stress was reduced, deflection was reduced, and stress distribution was more even. The CFRP layer helps resist tensile and compressive forces, thereby slowing crack formation and increasing the overall load-bearing capacity of the structure. These results conclude that the use of CFRP is effective in increasing flexural strength and reducing deflection in sengon laut wood beams. With its lightweight, strong, and easy-to-apply characteristics, CFRP has the potential to be an innovative solution for reinforcing sengon laut wood in economically and sustainably constructed residential buildings.